Control de inventario al Taller de Ebanistería JG - Gómez González, José Pablo (2021)
This case study focuses on the inventory control analysis of the JG cabinetmaker's workshop in the city of Montalvo, where there are certain peculiarities that cause said process to not be carried out correctly, generating from a professional point of view the lack of logistics in the entity. The methodology applied by the current research is of a descriptive-bibliographic nature, because, thanks to the information obtained by the different instruments such as the interview and the survey, the inconveniences that the organization has is detailed based on textual supports. The information described in the current document uses the deductive method, based on a general conclusion such as the Inventory Control of the aforementioned place, extracted from the phenomenon that generated in this case study, in order to determine the particular problems that arise. have been raised in the entity, during the period established in the investigation, in order to expose the main shortcomings, so that, based on a technical perspective, those in charge of the premises, take the appropriate strategies.